Dietary outcomes of community-based CVD preventive interventions: a systematic review and meta-analysis - Hamid Y Hassen; Binyam G Sisay; Jean-Pierre Van Geertruyden; Delphine Le Goff; Rawlance Ndejjo; Geofrey Musinguzi; Steven Abrams; Hilde Bastiaens (Cambridge University Press, 2023)
Abstract Objective: We aimed to synthesise available evidence on the effects of community-based interventions in improving various dietary outcome measures. Design: Systematic review and meta-analysis. Setting: We searched databases including Medline, EMBASE, PSYCINFO, CINAHL and the Cochrane registry for studies reported between January 2000 and June 2022. The methodological quality of the included studies was evaluated using the Cochrane risk of bias tools for each study type. For some of the outcomes, we pooled the effect size using a random-effects meta-analysis. Participants: A total of fifty-one studies, thirty-three randomised and eighteen non-randomised, involving 100 746 participants were included. Results: Overall, thirty-seven studies found a statistically significant difference in at least one dietary outcome measure favouring the intervention group, whereas fourteen studies found no statistically significant difference. Our meta-analyses indicated that, compared with controls, interventions were effective in decreasing daily energy intake (MJ/d) (mean difference (MD): -0·25; 95 % CI: -0·37, -0·14), fat % of energy (MD: -1·01; 95 % CI: -1·76, -0·25) and saturated fat % of energy (MD: -1·54; 95 % CI: -2·01, -1·07). Furthermore, the interventions were effective in improving fibre intake (g/d) (MD: 1·08; 95 % CI: 0·39, 1·77). Effective interventions use various strategies including tailored individual lifestyle coaching, health education, health promotion activities, community engagement activities and/or structural changes. Conclusion: This review shows the potential of improving dietary patterns through community-based CVD preventive interventions. Thus, development and implementation of context-specific preventive interventions could help to minimise dietary risk factors, which in turn decrease morbidity and mortality due to CVD and other non-communicable diseases.